Lycopene Supplementation Mitigates Heat Stress-Induced Impairment of Embryonic Development, Survival, and Heart Rate in Zebrafish (Danio rerio) - Residiwati, Gretania; Nararya, Winandana Parama; Ainurrahma, Hafidha; Lonameo, Bonick Kartini; Lesmana, Muhammad Arfan; Agustina, Galuh Chandra; Budiono; Hartono, Djoko; Hendrawan, Viski Fitri; Tuska, Habib Syaiful Arif; Sidi, Shehu (Faculty of Veterinary Medicine Universitas Brawijaya, 2026)
Fish at any change in aquaculture air temperature can affect fish survival, physiological conditions and immune response. The need to study the reaction of fish to sublethal temperatures (30-40oC) is an impetus because of global warming which can trigger heat stress (HS). Heat stress (HS) and its effects can occur in fish with any changes in the environment (physical or physiological), where heat can change the animal's normal homeostasis. Tomato (Lycopersicum esculentum), has been proven as a fruit that is rich in lycopene, which acts as a natural antioxidant. The purpose of this study was to determine the effect of lycopene supplementation on the process of external fertilization on embryo development, survival rate and heart rate of zebrafish (Danio rerio) at normal temperature (NHS) and with heat exposure (HS). The survival rate data obtained will then be analyzed using SPSS, with ANOVA and LSD tests (P ≤0.05). While the results of the statistical analysis test of heart rate, a non-parametric test was used using Kruskal-Wallis H, to find out whether there was a significant difference in the treatment; and the Mann-Whitney Test, to detect significant differences between groups (P ≤0.05). The effect of lycopene supplementation on the external fertilization process of zebrafish embryos gives a low survival rate and heart vibration of zebrafish embryos, which is thought to be caused by several factors, namely zebrafish genetics; storage method, dosage, and lycopene extraction method used in the research